PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI PADA RUMAH MAKAN TAMAN INDAH SOLO) - Radityo Narendra Dewanto; Hari Susanta Nugraha; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2025)
This research was conducted to examine the influence of product quality, service quality and price on consumer purchasing decisions at Taman Indah Solo Restaurant. Taman Indah Restaurant sales data shows fluctuations in income, and from the 23 months of Taman Indah Restaurant sales data listed, there are 13 months of sales data that did not meet the target. This research used explanatory research with a quantitative approach with a non-probability sampling technique using a purposive sampling method for 97 respondents at the Taman Indah Solo Restaurant. The data obtained is then processed through validity tests, reliability tests, coefficient correlation, determination correlation, simple linear regression tests, multiple linear regression tests, t tests, and f tests. The results of this research show that product quality, service quality and price influence consumer purchasing decisions at Rumah Makan Taman Indah Solo, and have a correlation between these variables on purchasing decisions. Together, product quality, service quality, and price influence consumer purchasing decisions at Taman Indah Solo Restaurant, and have a mutual correlation. The advice obtained from this research is that Taman Indah Restaurant needs to make a number of improvements in increasing product quality, service quality and prices. The improvements in question include the appearance of food and drink products and the temperature of food which must always be maintained, the service provided must be friendlier. and the cleanliness of the available facilities must be further improved, balancing the prices provided with the quality of food and beverage products.